IMPLEMENTATION OF INFORMATION TECHNOLOGIES IN INSTITUTIONS OF VOCATIONAL EDUCATION - Kodik Alla; Pohorielov Mykhailo (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The article covers the theoretical, methodical and practical aspects of the implementation of information technologies in vocational education and training. The purpose of the article is to find factors for improving the educational process, management, methods and information work via the introduction of information/information and communication technologies in institutions of vocational and technical education. The following methods were used in the research process: theoretical and substantive analysis of primary sources and advanced pedagogical experience, analysis, generalization and systematization of scientific approaches in the use of information and communication technologies in the educational process of vocational education institutions, as well as methods of modelling and designing the “Teacher’s Road Map”. It has been established that information/information and communication technologies in vocational education are an important area of activity of an educational institution and a tool for increasing the teacher’s productivity. It has been found out that the pedagogical terms contributing to the effectiveness of the use of information technologies in vocational education institutions are a high level of information culture of teachers and students; implementation of innovative technologies including information and communication pedagogical ones based on subject-subject interaction; ensuring the reflection of the subjects of the educational process, their capability of adequate self-assessment of their personality. A virtual road map for the teacher has been developed as an electronic public resource (for example, a website). The map shows all mandatory points and routes that a teacher should take during educational activities in a vocational education institution. The main directions in the teacher’s virtual road map which are consistent with the similar ones of the teacher’s activity in a real educational situation are defined. The virtual road map covers educational and methodical work, has a hyperlink to the plan of methodical work of the cycle commission for the year, a hyperlink to methodical manuals or guides on the organization work in a vocational education institution; provides teachers with system suggestions and hyperlinks to electronic educational resources; a hyperlink to cloud storage for downloading documents for advanced training courses or internships; certificates, diplomas regarding participation in scientific and methodical events and self-education; a hyperlink to the cloud storage for uploading planning documents and methodological developments for review and approval. The virtual road map is differentiated by subject area which allows for providing meaningful instructions to occupational safety teachers, road safety teachers, industrial training masters, and teachers of special disciplines. The result of the research is the development of a meaningful module “Digital technologies in education: cloud services, online platforms for the creation of an educational environment by the teacher and the improvement of the qualifications of the pedagogical staff of the vocational educational institution.” It has been concluded that due to the testing of the information educational environment model at the Kostyantyniv Higher Vocational School, the approaches to the internal management of the institution, the organization of methodical, educational and study work, the forms and methods of teaching the profession, the culture of designing theoretical and industrial training lessons, the system assessment of educational achievements of students, and ways of involving parents in the educational process at the institution have been enhanced.